2020
DOI: 10.1101/2020.06.04.132175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Providing recombinant gonadotropin-based therapies that induce complete oogenesis and produce viable larvae from an immature teleost, flathead grey mullet (Mugil cephalus)

Abstract: Under intensive captive conditions, wild-caught flathead grey mullet (Mugil cephalus) 12 females remain arrested at early gonad development and males do not produce sperm. With the aim to induce gametogenesis and obtain fertilized eggs, adult female and male 14 grey mullet were treated with M. cephalus single-chain recombinant gonadotropins (rGths), follicle-stimulating (rFsh) and luteinizing (rLh) hormones. In Experiment 1, a 16 weekly dose of rFsh (15 µg kg -1 ) significantly (P < 0.001) increased plas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The economic importance of Mugil is based on its consumption and its cost varies from one region to another, relying on several factors; for example, female’s grey mullet gonads, also known as caviar or bottarga, could reach 65 € per kg in the European markets (Aldana, 2015; Rodríguez, 2018). Therefore, significant advances have been made on nutrition, growth, larval culture and reproduction of individuals reared in captivity (Martínez et al ., 2019; Talukdar et al ., 2020; Besbes et al ., 2020; Ramos-Júdez et al ., 2021). Furthermore, several studies have demonstrated that grey mullet can also be an adequate candidate species for mariculture which can contribute to food production and the reduction of fishing impact (Saleh, 2008; Robles & Mylonas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The economic importance of Mugil is based on its consumption and its cost varies from one region to another, relying on several factors; for example, female’s grey mullet gonads, also known as caviar or bottarga, could reach 65 € per kg in the European markets (Aldana, 2015; Rodríguez, 2018). Therefore, significant advances have been made on nutrition, growth, larval culture and reproduction of individuals reared in captivity (Martínez et al ., 2019; Talukdar et al ., 2020; Besbes et al ., 2020; Ramos-Júdez et al ., 2021). Furthermore, several studies have demonstrated that grey mullet can also be an adequate candidate species for mariculture which can contribute to food production and the reduction of fishing impact (Saleh, 2008; Robles & Mylonas, 2017).…”
Section: Introductionmentioning
confidence: 99%